Not the end of the world - McCaughrean, Geraldine (Oxford : Oxford University Press, 2005)
Noah's daughter, daughters-in-law, sons, wife, and the animals describe what it was like to be aboard the ark while they watched everyone around them drown.
Young Adult.
Young Adult
Keywords: Noah, -- (Biblical figure -- Juvenile fiction; Noah, -- (Biblical figure -- Fiction; Noah, -- (Biblical figure -- Fiction; Bible -- History of Biblical events -- Fiction; Large type books; Noah's Ark -- Fiction; Noah's Ark -- Fiction; Noah's Ark -- Fiction; Bible fiction